Efektifitas Media Audio Visual (Video) Untuk Meningkatkan Ketrampilan Pemeriksaan Fisik Pada Mahasiswa S1 Keperawatan - Siti Munawaroh; Sujiono -; Vivi Yosafianti Pohan (Jurnal Keperawatan Muhammadiyah, 2019)
Physical examination is one of the competencies, that is must be mastered by nursing students. The truth and accuracy of physical examination is the key to success in the implementation of nursing care. Many media can be used to understand of physical examination  material, one of which is Audio Visual Media (video). The purposif of this study is to the use of Audio Visual Media (video) on the Teaching and Learning process of Physical examination in the Undergraduate Students of NursingThe research design was Quasy-eksperiment with pre test and post test design. The sample was 103 respondens in the pre-test group and 103 respondents in the post-test group. Sampel recruited by total sampling. Data  were analyxed using the  t dependent test.The average to perform of physical examination before the responden given video was 24,70 white deviation standart was 7,52. The average to perform of physical examination after the responden given video was increase, that average was 40,15 and deviation standart was 8,76. The t dependent test result showed pvalue=0,000 (pvalue<0,05)..It is concluded that there was a significant difference to perform of physical examination before the responden given video and after the responden given video. Futther research is expected to use a control group.